Operationalization of the Decentralized Policy Framework in Uganda: An Examination of the Key Milestones and Challenges. - Mugavu, George; Mucunguzi, Abel (Kabale University, 2024)
Decentralization in Uganda has been considered one of the most instrumental and partly successful policies amongst most of the policies that have been implemented under the National Resistance Movement Government. This is attributed to a well streamlined governance structure with connected checks and balances in case of any breach of the rules of procedure of implementation on providing services by a particular individual or individuals working or acting in a particular local government office. Of course there are governance challenges notably corruption, bribery and embezzlement of funds, political pressures and patronage all of which deter local governments from achieving their set goals and objectives. In this paper we attempt to review and assess the governance of the decentralization policy in Uganda concentrating on the key milestones and failures.